2011
DOI: 10.1167/iovs.10-5349
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Corneal Mechanical Adaptation in Contact Lens–Related Dry Eye Symptoms

Abstract: PURPOSE.To compare corneal mechanical adaptation measured psychophysically in contact lens wearers with or without dry eye symptoms. METHODS. Two groups of contact lens wearers were recruited. One group (symptomatic) consisted of subjects with dry eye symptoms (according to the subjective evaluation of symptom of dryness [SeSoD] questionnaire). The second control group (asymptomatic) consisted of subjects reporting no symptoms. There were 32 (aged 20 to 42 years, 6 males and 26 females) and 29 subjects (aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…These results also run counter to the cornea and lacrimal gland feedback model proposed by Mathers (Mathers, 2000), in which it was hypothesized that dry eye produces a decrease in the sensitivity of corneal primary afferent neurons. The effect of dry eye on the properties of mechanoreceptive and polymodal neurons has not been examined, yet sensitization of these neurons would be consistent with studies that have reported significant hyperesthesia in individuals symptomatic for ocular dryness (Chen and Simpson, 2011; De Paiva and Pflugfelder, 2004; Situ et al, 2008a; Situ et al, 2008b; Tuisku et al, 2008)(but see (Benitez-Del-Castillo et al, 2007; Bourcier et al, 2005; Stapleton et al, 2006)).…”
Section: Properties Of Corneal Sensory Neurons In Dry Eyesupporting
confidence: 57%
“…These results also run counter to the cornea and lacrimal gland feedback model proposed by Mathers (Mathers, 2000), in which it was hypothesized that dry eye produces a decrease in the sensitivity of corneal primary afferent neurons. The effect of dry eye on the properties of mechanoreceptive and polymodal neurons has not been examined, yet sensitization of these neurons would be consistent with studies that have reported significant hyperesthesia in individuals symptomatic for ocular dryness (Chen and Simpson, 2011; De Paiva and Pflugfelder, 2004; Situ et al, 2008a; Situ et al, 2008b; Tuisku et al, 2008)(but see (Benitez-Del-Castillo et al, 2007; Bourcier et al, 2005; Stapleton et al, 2006)).…”
Section: Properties Of Corneal Sensory Neurons In Dry Eyesupporting
confidence: 57%
“…43 A more recent investigation found corneal adaptation to suprathreshold stimuli in asymptomatic SCL wearers but not in symptomatic wearers, although there was no difference in thresholds between the 2 groups. 44 All these findings show that the understanding of the relationship between CLD and sensitivity of the ocular surface is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous results, 11,12 sensitivity in the asymptomatic group tended to be reduced compared to controls suggesting neural adaptation. 19 In contrast, the symptomatic group was the most sensitive.…”
Section: Discussionmentioning
confidence: 94%
“…39 These suggest the development of sensitization and the alteration of neural control of the functional unit in symptomatic wearers, 40 although maybe additional adaptation mechanisms could also affect the sensory processing in symptomatic wearers. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation